Early Complications after Thyroid Surgery: An Observational Study (Central Medical College Journal, 2025)
Background: Thyroid operations are often crucial for managing thyroid conditions. Surgical treatment depends on the goitre and the type of patient presented during treatment. While effective, thyroid surgery carries certain risks. Common early surgical complications include hypocalcaemia, infection, hematoma, and laryngeal nerve palsy, any of which can pose significant health risks for patients. Objective: The paper pointed out the immediate complications after thyroid surgery. Methods and Materials: This prospective study was conducted in the ENT outdoor and indoor department of the Comilla Medical College from 1 January 2023 to 31 December 2023. Sixty patients who were admitted for thyroid surgery were selected. Each patient was monitored for one month post-surgery to document any complications that arose, which were noted and analysed. Results: Complications were observed in 15 patients (25%). Recurrent laryngeal nerve injury was the most common complication in 13.33% (n=8) of cases, followed by hypocalcaemia at 6.66% (n=4). Hypocalcaemia was associated with thyroid cancer in 3 cases (13.63%). Complications were predominantly linked to malignant tumours, the extent of surgical intervention, and the surgeon's skill level. Conclusion: Careful dissection, accurate identification, and preservation of the laryngeal nerves and the parathyroid gland are essential to reducing complication rates. A solid understanding of anatomy and proficient surgical techniques are critical factors in minimizing risks.Central Medical College Journal Vol 8 No 2 July 2024 Page: 64-69